Uncovering Historic and Modern Discrepancies in the Paleo Diet - Dorothy Agoulnik (Tufts University. Tisch Library., 2020)
The PD is primarily adopted to combat current maladaptation to industrialized diets, which contribute to chronic disease risk. The aims of this study are 1) to evaluate fiber and total energy intake among randomized controlled trials (RCTs) and observational studies using a PD 2) to evaluate fiber and total energy intake among self-reported adheres of the PD 3) to understand how populations are adhering to the principles of the PD by evaluating the PD with gluten-free and dairy-free diet groups. The following study demonstrates there are major discrepancies in the historic, hypothetical, and modern implementations of the PD.; Gerald J. and Dorothy R. Friedman School of Nutrition Science and Policy at Tufts University; Boston, MA USA Defense Date: April 29, 2019; Thesis Committee: Nicola M. McKeown, Elena Naumova, Mathieu Lalonde; Thesis (M.S.)--Tufts University, 2019.